PERAN LINGKUNGAN BAHASA ARAB UNTUK MENINGKATKAN KETERAMPILAN BERBICARA PADA SANTRI PONDOK PESANTREN BABUL KHAIRAT PASURUAN - Nismah, Nevin; Rosyidi, Abdul Wahab; Mufidah, Nuril (Sekolah Tinggi Agama Islam Raudhatul Ulum, 2025)
The Arabic language environment plays an important role in improving students' speaking skills, so creating a language environment becomes the main strategy in learning. This research aims to determine the design as well as supporting and inhibiting factors in implementing the Arabic language environment. This research uses a qualitative case and field study approach, with data collection techniques through interviews, observation and document analysis. The research subjects were class students Tsani Tsanawi 2025/2026 academic year as many as 20 people and Arabic language teachers. Data analysis uses the model from Miles & Huberman, namely data collection, data presentation and conclusions. The research results show that the Babul Khairat Islamic Boarding School applies formal and informal designs. Formal design includes classroom learning, while informal design includes language programs. A system of rewards and punisments is also implemented to increase student motivation. Supporting factors include student motivation, teacher support, and an active community, while obstacles are lack of practice, limited access, and low student self-confidence. This research found that the informal design is more effective, because it is easier for students to practice and get used to using Arabic in daily interactions through the programs that have been provided.